Faktor Yang Berhubungan Dengan Keluhan Gangguan Pernapasan Pada Pemulung Di Tempat Pembuangan Akhir Sampah (TPAS) Tamangapa Kota Makassar - Raihanah, Nurul Dzakylah; Yuliati; Sani, Andi (Window of Public Health Journal, 2025)
Waste management that does not comply with regulations will cause environmental and human health problems. The development of disease vectors and air pollution that can interfere with the breathing of scavengers are the most common waste management problems at the Final Waste Disposal Site (TPAS). Complaints from scavengers regarding respiratory problems at the Tamangapa Final Waste Disposal Site (TPAS) in Makassar City are the objectives of this study, which seeks to identify variables related to these complaints. Quantitative research is the method used in this study, using a cross-sectional approach. The sample collection method is total sampling, which includes all scavengers at the Tamangapa Final Waste Disposal Site (TPAS) in Makassar City, totaling 101 scavengers. The chi-square test was used to analyze the data with a 95% confidence level. Based on the research findings, complaints of respiratory problems correlate with the use of masks (p = 0.000), length of work (p = 0.001), and medical history (p = 0.004) with complaints of respiratory problems. Meanwhile, respiratory complaints did not correlate with smoking habits (p=0.829) and length of service (p=0.190) with respiratory complaints. The results of this study expect scavengers to pay more attention to their health by reducing working hours, wearing masks while working, checking their health with health workers, and implementing a healthy lifestyle to minimize the risk of respiratory complaints.